In vitro characterization of the a-thalassemia point mutation HBA2:c.95+1G>A [IVS-I-1(G>A) (a2)] - Qadah, T.; Finlayson, J.; Ghassemifar, Reza (2012)
The a-thalassemias are a group of disorders occurring as a result of decreased synthesis of a-globin chains, most commonly due to deletions of a-globin genes. Detection of a-thalassemia (a-thal) caused by point mutations has increased during the past few years and more than 70 different point mutations have been reported for the a1- and a2-globin genes. The mutation at the splice donor site of the first intervening sequence [IVS-I-1 (G>A)] of the a2-globin gene, HBA2:c.95+1G>A, is thought to cause a thalassemic phenotype by interfering with and preventing the normal splicing of pre-mRNA. We developed an in vitro expression system to study a-globin gene point mutations at the molecular and cellular levels. The expression vector carrying the HBA2:c.95+1G>A mutation (a2G IVS-I-1G>A) was created using site-directed mutagenesis of a wild type (WT) construct of the a2-globin gene (a2G 2034WT). Gene expression experiments in human bladder carcinoma 5637 cells were carried out using sequence verified WT and mutated clones. Complementary DNA synthesis and polymerase chain reaction (PCR) analysis showed normal a2-globin transcripts from cells transfected with the WT vector, but aberrant transcripts from cells transfected with the mutated vector carrying the splice donor site mutation. In the presence of the G>A mutation, normal splicing does not occur, and a cryptic splice site 49 bp upstream of the normal site is used. The translation of this product produces a premature termination codon, thus resulting in a thalassemic phenotype. © 2012 Informa Healthcare USA, Inc.